A CASE STUDY ON THE IMPACT OF INDUSTRIAL EFFLUENT DISPOSAL ON THE FISHERY OF AMBA RIVER ESTUARY, MAHARASHTRA - GAJBHIYE, S. N.; MEHTA, PRATIK; MUSTAFA, S.; NAIR, VIJAYALAKSHMI R. (Journal of Indian Fisheries Association, 2006)
The impact of waste discharge on fishery resources IS a n1.atter of great concern. The accepted norm in all environmental impact assessment studies is to avoid areas of high fishery potential while locating a marine outfall. Contemplating on this aspect a case study was conducted in the Amba River estuary before and after the establishment of a petrochemical complex at Nagothane. The treated wastewater from this complex is released through a subsurface outfall after adopting effective control measures for marine disposal of waste. Experimental trawling was done at five locations covering a distance of 30 km during 1990 to 1991. The catch rate within the estuary varied from 0.6 to 255 kg/h (av 24 kg/h). The trend indicated considerable decrease in fishery potential from the mouth of the estuary (av 64 kg/h) to the upstream location (av 11 kg/h). A total of 49 species of fishes, 16 species of prawns, 7 species of crabs and 1 species of lobster were identified from the collections. Nu:mber of species gradually increased from the interior segment at Dharamtar (8) to the outer area near Revas (18). A comparison of the quantitative and qualitative nature of the post outfall and preoutfall data revealed only marginal difference. The study indicates that if necessary precautions are taken to render the waste harmless the n1arine ecology will hardly be affected.